Optimalisasi Kebijakan Penurunan Stunting Melalui Program Bimbingan Perkawinan dan Keluarga - Haikal, Muamar (JURNAL ILMIAH GEMA PERENCANA, 2024)
This policy paper describes that the main actors in the stunting reduction policy in Indonesia are families through Marriage and Family Guidance in Islamic, Christian, Catholic, Hindu, Buddhist, and Confucian communities. Based on the evaluation and findings, a review of this policy and program is needed. The findings in this paper indicate that there is potential for ineffectiveness in the stunting reduction program. The purpose of this paper is to evaluate the effectiveness of the Ministry of Religious Affairs's policy on the marriage and family guidance program in reducing stunting rates. The results show that there are various factors that cause the performance of the stunting reduction budget to be suboptimal, namely the inaccurate preparation of performance indicators and the lack of coordination of budget planning with related work units. For this reason, the author recommends the importance of (1) providing training for employees or human resources in the planning bureau or work units related to planning and budgeting at the Ministry of Religious Affairs related to stunting reduction; (2) carrying out coordination and collaboration related to budget planning by involving the Planning Bureau with related work units regarding the suitability of budget logic and performance indicators in reducing stunting; (3) create policies on reducing stunting at the Ministry of Religious Affairs by optimizing the Marriage and Family Guidance program through rational, effective, accurate, and targeted budget acceleration, so that the impact can be felt directly by the community.